Wise family papers
Chiefly correspondence of Henry Alexander Wise relating largely to the John Brown raid. Includes letters (1905) of Albert Bushnell Hart. Correspondents include John C. Calhoun, Leslie Combs, John W. Forney, Amos C. Lawrence, John C. Rives, William B. Taliaferro, Nathaniel Beverley Tucker, Jr., and Wise's cousin, Henry Augustus Wise.
Microfilm edition of selected correspondence available
Microfilm produced from originals in the Manuscript Division.
In part, transcripts and negative photocopies.
Wise family including Henry Alexander Wise, U.S. representative, governor of Virginia, and Confederate Army officer and Henry Augustus Wise, naval officer and author.
Collection material in English.
Keywords: Brown, John, -- 1800-1859 -- Correspondence; Calhoun, John C. -- 1782-1850 -- Correspondence; Combs, Leslie, -- 1793-1881 -- Correspondence; Forney, John W. -- 1817-1881 -- Correspondence; Hart, Albert Bushnell, -- 1854-1943 -- Correspondence; Rives, John C. -- 1795-1864 -- Correspondence; Tucker, Nathaniel Beverley, -- 1820-1890 -- Correspondence; Wise, Henry A. -- 1806-1876 -- Correspondence; Wise, Henry A. -- 1819-1869 -- Correspondence; Wise family; Confederate States of America. -- Army; Harpers Ferry (W. Va.) -- History -- John Brown's Raid, 1859.; Lawrence, Amos C. -- Correspondence; Taliaferro, William Booth, -- 1822-1898 -- Correspondence